Noninvasive Detection of Active Microcalcification in an Occlusive Peripheral Vascular Aneurysm Using 18F-NaF PET/CT Imaging. (December 2020) - Eisert, Susan Natalie; Chou, Ting-Heng; Bobbey, Adam J.; Go, Michael R.; Stacy, Mitchel R.
Abstract : Abstract: A 65-year-old man with an occluded popliteal artery aneurysm and calf claudication underwent PET/CT imaging with 18 F-NaF to assess the status of active microcalcification in the aneurysm site and additional lower extremity arteries. CT imaging revealed macrocalcification of the aneurysm that colocalized with elevated retention of 18 F-NaF on PET images. PET/CT detected additional distal arterial sites with focal uptake of 18 F-NaF that did not coincide with CT-detectable macrocalcification. This report highlights a case of active microcalcification in an occlusive peripheral aneurysm using PET/CT. PET/CT may provide molecular insight into the remodeling of lower extremity aneurysms and atherosclerotic lesions.